Sangria Aberta ou Artéria do Progresso: A emigração ibérica oitocentista nos debates sobre a colonização do além-mar - Gonçalves, Paulo Cesar [UNESP] (My University, 2013)
Using documents produced by the Geographical Society of Lisbon and the Geographical Society of Madrid, and studies of some of theirs most important members, this article focuses on the importance of emigration in the nineteenth century Iberian debates within the two entities on issues as empire, colonization and economic development of both countries.
Progressive artery or open bleeding: The nineteenth century Iberian emigration in the debates on overseas colonization
Keywords: Colonization; Emigration; Geography; Portugal; Spain